2018
DOI: 10.1007/s10545-018-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for Pompe disease: impact on families

Abstract: Pompe disease (PD) is an autosomal recessive lysosomal storage disorder causing progressive glycogen accumulation in muscles, with variability in age of onset and severity. For infantile-onset PD (IOPD), initiation of early treatment can be life-saving; however, current newborn screening (NBS) technology cannot distinguish IOPD from late-onset PD (LOPD) without clinical workup. Therefore, families of LOPD infants diagnosed by NBS may now spend years or even decades aware of their illness before symptoms appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 29 publications
6
38
1
Order By: Relevance
“…High stress and anxiety at initial phone call were reported by nearly all participants in this study. These results are consistent with studies looking at the parental NBS experience for other diseases, such as Pompe disease (PD) and cystic fibrosis [9,10]. Given the myriad of negative emotions experienced by parents upon learning their child's positive screening results, HCPs who work with these families should be aware of the factors that contribute to a positive, informative, and supportive NBS experience, in the context of a potentially devastating diagnosis.…”
Section: Educating Healthcare Providers On Aldsupporting
confidence: 82%
See 2 more Smart Citations
“…High stress and anxiety at initial phone call were reported by nearly all participants in this study. These results are consistent with studies looking at the parental NBS experience for other diseases, such as Pompe disease (PD) and cystic fibrosis [9,10]. Given the myriad of negative emotions experienced by parents upon learning their child's positive screening results, HCPs who work with these families should be aware of the factors that contribute to a positive, informative, and supportive NBS experience, in the context of a potentially devastating diagnosis.…”
Section: Educating Healthcare Providers On Aldsupporting
confidence: 82%
“…Given the myriad of negative emotions experienced by parents upon learning their child's positive screening results, HCPs who work with these families should be aware of the factors that contribute to a positive, informative, and supportive NBS experience, in the context of a potentially devastating diagnosis. This sentiment is shared by parents of children who received positive NBS results for PD, as studied by Pruniski et al [9]. As with ALD, the parents of these children felt that the HCP making the initial disclosure was not fully informed on PD.…”
Section: Educating Healthcare Providers On Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, after confirmation of LOPD, uncertainty exists for parents and specialty caregivers as there is currently no established management guideline for presymptomatically-identified LOPD infants. Our family's experience mirrors closely those of other families receiving Pompe disease NBS results [21]. As additional LOPD cases are identified and followed longitudinally with existing NBS-identified LOPD cases, a clearer natural history, prognosis, and recommendations for timing of treatment initiation will arise.…”
Section: Discussionmentioning
confidence: 53%
“…In a study that examined the effects of positive newborn screening results on families; it was reported that uncertainty caused anxiety, and while the uncertainty was increasing, families' anxiety was also increasing (42). Parental anxiety increases as the risk and unknownness of the procedure is increased.…”
Section: Discussionmentioning
confidence: 99%